Reimagining Waqf-Based Entrepreneurship: Building Inclusive Islamic Business Ecosystems for Sustainable Economic Growth - Namungo Hamzah; Adamu Abubakar Muhammad; Ismail Iliyasu Danladi; Babangida Bala; Abdullah A. Afifi; Muhammadu Sani Abubakar (IDRIS Darulfunun Institute, 2025)
Entrepreneurship has been widely acknowledged as a significant engine for job creation, innovation, poverty reduction and inclusive economic growth in recent times. For developing economies, particularly small and medium-sized enterprises (SMEs), entrepreneurship fosters overall economic resilience and sustainable development. Despite the critical role of entrepreneurship, many aspiring entrepreneurs continue to face substantial challenges such as limited access to finance, poor business support services, a lack of technical expertise, weak institutional networks, and confined markets. Often, classical modes of financing have excluded a significant proportion of the most disadvantaged groups because of their collateral requirements, high finance costs, and poor capital access. From an Islamic economic viewpoint, waqf has long served diverse purposes; however, in most instances its function has mostly focused on education, business ventures, community infrastructure and the welfare of society. The purpose of this article is to conceptualize how waqf can be redefined as a sustainable institution to enhance entrepreneurship development and build inclusive Islamic entrepreneurial ecosystem. This paper proposes the Waqf-Based Entrepreneurship Ecosystem Framework (WBEEF) that encompasses productive waqf, entrepreneurship development, business incubation, Islamic finance, digital innovation, and institutional collaboration to support sustainable enterprise creation and enhance sustainable economic resilience. The present study used qualitative research methods and followed documentary analysis and literature review method. In this regard, both classical Islamic legal sources and modern literatures of waqf, Islamic economics, entrepreneurship, SME development, business ecosystem theory, innovation and sustainable development have critically analyzed. Through a conceptual and analytical analysis of existing literature, an integrated research has carried out linking Islamic philanthropic institutions to the development of entrepreneurial ecosystem. This study identifies that productive waqf has significant potential to foster entrepreneurship by providing seed capital, vocational training, business incubation centres, shared facilities, market development initiatives, research and innovation hubs, digital infrastructure, and other business development support services. Furthermore, an integration of waqf with Islamic banks and other Islamic financial institutions, universities, government agencies, technology organizations, business associations, and corporations could stimulate local entrepreneurial capabilities, alleviate financial exclusion, and facilitate sustainable business development. The WBEEF has built productive partnerships amongst these actors to develop youth ventures, women-owned businesses, halal and green enterprises, agricultural innovations, and social entrepreneurships, which foster economic opportunities, technology, wealth generation and economic growth within Islamic ethical framework of social justice, equity and responsibility. This paper, by conceptualizing a new framework in the context of Islamic economics, presents an original contribution in repositioning the institution of waqf from its conventional perception as only for charitable/religious affairs towards a sustainable entrepreneurial resource for inclusive business growth and socio-economic development. The Waqf-Based Entrepreneurship Ecosystem Framework (WBEEF) provides an innovative practical guideline and policy agenda for waqf institutions, Islamic finance organizations, government and public sector authorities, policy makers, entrepreneurs and development actors in leveraging waqf resources for strengthening SMEs development, job creation, poverty reduction and economic resilience in conformity with the broader social welfare objectives of Islamic economics.